2020
DOI: 10.1101/2020.12.02.408153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LL-37 fights SARS-CoV-2: The Vitamin D-Inducible Peptide LL-37 Inhibits Binding of SARS-CoV-2 Spike Protein to its Cellular Receptor Angiotensin Converting Enzyme 2In Vitro

Abstract: Objective: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the pathogen accountable for the coronavirus disease 2019 (COVID-19) pandemic. Viral entry via binding of the receptor binding domain (RBD) located within the S1 subunit of the SARS-CoV-2 Spike (S) protein to its target receptor angiotensin converting enzyme (ACE) 2 is a key step in cell infection. The efficient transition of the virus is linked to a unique protein called open reading frame (ORF) 8. As SARS-CoV-2 infections can develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…A recent in silico molecular docking study predicted a strong binding interaction between LL-37 and the RBD, demonstrating the blocking potential of LL-37 for ACE2 binding (Lokhande, 2020). This was followed up by a surface plasmon resonance study confirming the simulation results (Roth et al, 2020). Since LL-37 has also been shown to possess antiviral activity (Tripathi et al, 2015), these results support the idea that more than one AMP could be utilized, possibly in a "cocktail" to act as a potent viral blocking agent.…”
Section: Discussionsupporting
confidence: 75%
“…A recent in silico molecular docking study predicted a strong binding interaction between LL-37 and the RBD, demonstrating the blocking potential of LL-37 for ACE2 binding (Lokhande, 2020). This was followed up by a surface plasmon resonance study confirming the simulation results (Roth et al, 2020). Since LL-37 has also been shown to possess antiviral activity (Tripathi et al, 2015), these results support the idea that more than one AMP could be utilized, possibly in a "cocktail" to act as a potent viral blocking agent.…”
Section: Discussionsupporting
confidence: 75%
“…Human cathelicidin LL-37 was recently reported to bind to the region binding domain (RBD) of the Spike protein of SARS-CoV-2 coronavirus [ 12 ]. Using the COVID-19 docking server, we submitted the bat cathelicidin peptide models to an analysis of their interaction with the RBD domain of the SARS-CoV-2 Spike protein.…”
Section: Resultsmentioning
confidence: 99%
“…A biochemical relation between vitamin D, LL-37 and COVID-19 intensity has been suggested for the human cathelicidin LL-37. Surface Plasmon Resonance research has shown that LL-37 binds to SARS-CoV-2 S protein and prevents binding to its hACE2 receptor, and most likely viral entry into the cell [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…By regulating chemokine and cytokine production, both AMPs help to maintain homeostasis of the immune system and display antiviral properties, as for example evidenced by gene regulation upon viral challenge or expression in cells involved in viral defense (Wilson et al, 2013). LL-37, consisting of 37 amino acids and an overall positive net charge (+6) can also eliminate microbes directly by electrostatic binding to negatively charged molecules on microbial membranes (PrePrint Roth et al, 2020). In secretions from lung and nose it was found that LL-37 could reach high concentrations indicating to a relevant role in lung immune defense mechanisms (Kim et al, 2003;Mansbach et al, 2017;Schaller-Bals et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of AMPs on virus infections appear to be specific to the virus, AMP, and also target cell and to our knowledge, a direct antiviral efficacy of HBD-1 or LL-37 against SARS-CoV-2 has not been shown so far (Ding et al, 2009). However, interestingly, for LL-37 a binding to the SARS-CoV-2 spike protein and an inhibitory action of LL-37 on the spike protein to its entry receptor have been reported using binding competition studies (PrePrint Roth et al, 2020). In another study, high structural similarity of LL-37 to the N-terminal helix of the receptor-binding domain of SARS-CoV-2 was reported (PrePrint Kiran Bharat Lokhande, 2020).…”
Section: Discussionmentioning
confidence: 99%